DAKWAH ADVOKASI KEBIJAKAN (IMPLEMENTASI PERATURAN DAERAH NO.2 TAHUN 2007 DI KECAMATAN SUNGAI TARAB) - Irwandi Irwandi (Alfuad: Jurnal Sosial Keagamaan, 2017)
Dakwah Advocacy Policy (Implementation of Local Regulation No.2 of 2007 in Sungai Tarab Subdistrict) Tanah Datar Regency Regulation number 2 of 2007 is stipulated as one effort to realize the desire of local government and society to implement the vision and mission of Tanah Datar Regency especially in improving the practice of religious values to realize the quality of faith and devotion of the people who are famous for the philosophy of Adat Basandi Syarak, Syarak Basandi Kitabullah. Based on the background, Sungai Tarab Subdistrict as one of the areas in Tanah Datar Regency seeks to implement the law with various forms of activities that encourage the implementation of this regulation as well as possible. This research uses Qualitative method. The results show that the Implementation of Local Regulation No. 2 of 2007, especially in Sungai Tarab Subdistrict has been implemented but in the implementation there are still the following things: For Students On Primary And Secondary Education And Bridal Candidates, substantially accompanied by academic script, which contains -those aspects of philosophy, sociology and juridical this is also related to the excavation and assessment of problems and needs of the community so that the problem to be solved by the regional regulation is not accommodated well, the socialization of the implementation of the local regulation is not done well, causing the interpretation different from the implementation of existing regulations so that the quality of implementation of this local regulation is less positive response from the community, on the one hand this regulation is often ignored, funding support from the local government is still not sufficient to support all components or contents from the implementation of the regulation, the Implementation of Perda in Sungai Tarab Sub-District as a whole has been in operation although in reality there are some provisions that exist in the regulation has not been implemented optimally caused by the limitations of Human Resources which become the object of the implementation of the Regional Regulation